The Influence Of Supervising Lecturer's Professional Practice On The Efficiency Of Trainee Teachers During Teaching Training - Sukardi , Shukiman (Ta'dib: Jurnal Pemikiran Pendidikan, 2021)
This study aims to examine the Influence of Professional Practice of Supervising Lecturers on the Effectiveness of Trainee Teachers during Teaching Training. The main focus of this study is to identify the four elements of guidance in the Professional Practice of Supervising Lecturers, namely Planning, Implementation, Reflective Practice and Attitude & Personality as well as its influence on the effectiveness of teachers throughout teaching practice. The objective of this study is to identify the level of Professional Practice of Supervising Lecturers and the Level of Teacher Effectiveness. In addition to identify the differences, relationships and influence of the professional practices of supervising lecturers on the effectiveness of trainee teachers during teaching practice. The respondents of the study are PDPP Trainee Teachers of Islamic Education Taken in June 2018, a total of 95 people. The design of this study is a descriptive type of survey that uses a questionnaire instrument. The questionnaires used were the Supervising Lecturer Professional Practice Form (α = 0.87) and Teacher’s Sense of Efficacy Scale - TSES (α = 0.86). The data obtained from the questionnaire were analyzed according to mean, standard deviation, t-test, correlation and regression using SPSS (Statistical Package For Social Science (SPSS 23.0). that the Professional Practice of Supervising Lecturers (mean = 4.85) and Teacher effectiveness (mean = 4.67) are very high, while there is no significant difference in the Professional Practice of Supervising Lecturers on gender (t value (95) = 0.36, p> 0.05). relationship, there is a strong positive relationship between Supervising Lecturer Guidance with Trainee Teacher Effectiveness (r = 0.78, p = 0.00) .Furthermore, the Professional Practice of Supervising Lecturer is a predictor of Teacher Effectiveness significantly, [F (1, 93) = 88.61, p <0.05] contributed a 48.8% variance (R2 = 0.488) in the teacher effectiveness score.Further suggestions were also recommended including expanding the study variables and using larger data, increasing tkan study population, study design should be detailed such as using Longitidunal and cross sectional study design. In addition, descriptive and inferential statistical analysis needs to be diversified to obtain a more accurate analysis of study results.